STUDENTS’ ENTREPRENEURIAL INTENTIONS DURING THE COVID-19 PANDEMIC IN THE CONTEXT OF THE DARK TRIAD TRAIT - Anyebe, Daniel; Kosmaczewska, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2023)
Aim: Despite research on how the constellation of the dark triad traits relates to entrepreneurial intention, it still remains to be seen how nuanced such relationships were during the COVID-19 pandemic in Europe. In this article, we investigate this phenomenon by elaborating on the relations between components of the dark triad traits concerning pull and push factors affecting entrepreneurial intention. Methods: Using 4,056 datasets from the Global University Entrepreneurial Spirit Students’ Survey (GUESSS) 2021 and data on unemployment rates and GDP per capita of 22 European countries, we employed multivariate regression analysis to examine the antecedents of entrepreneurial intention. Results: Our results show that GDP per capita is inversely related to entrepreneurial intention, with statistical significance also found for the unemployment rate and narcissism in their influence on entrepreneurial intention. More so, we found that COVID-19 unlocked the hidden potential of student entrepreneurship for the represented European countries. We also found interesting results on how the intensities of the dark triad influence entrepreneurial intentions. Conclusions: Difficult situations such as COVID-19 might trigger the manifestation of dark triad traits, which – to a greater extent – influence entrepreneurial intentions.